Comparison of benthic diatom community structures on natural and artificial substrates in marine lake (Adriatic Sea) - Car, Ana (Array, 2021)
In this study, the diatoms of three alternative habitats (epilithon, epiphyton and artificial sub-strate) were compared to understand the differences in composition on artificial and natural sub-strates. For this purpose, the samples were collected weekly between 11th August and 2nd Septem-ber 2016 at a sampling site in a shallow marine lake, Mrtvo More (Dead Sea) on Lokrum Island near Dubrovnik (South Adriatic, Croatia). In addition to detailed light microscopic analysis, ultrastructural analysis of benthic diatoms from Lake Mrtvo More was performed for the first time using scanning electron microscopy (SEM). A total of 97 taxa were identified in 12 samples. Cocconeis scutellum Ehrenberg and Halamphora coffeiformis (C.Agardh) Levkov were the most frequent taxa in the samples. Shannon-Wiener diver-sity index (H") values varied from 1.78 (in September on Padina sp.) to 4.52 (in August on glass). According to non-metric multidimensional scaling ordination, there were two groups: epilithon and artificial glass substrate as Group1 and macroalgae as Group2. The results of the analysis showed that the diatom communities developing on artificial sub-strates accurately correspond to the diatom community of a rock substrate and thus can be used as a representative alternative tool for studies of epilithic diatoms in further experiments.